Влияние функции щитовидной железы на гиперпластические процессы эндометрия у женщин репродуктивного возраста - Авраменко, Н. В.; Кабаченко, Е. В.; Барковский, Д. Е.; Авраменко, Наталія Вікторівна; Кабаченко, Олена Володимирівна; Барковський, Дмитро Євгенович; Avramenko, N. V.; Kabachenko, O. V.; Barkovsky, D. E. (Запоріжжя, 2016)
Обследовано 62 женщины возрастом от 18 до 55 лет, поделенных на две рандомизованные группы. В І гр. были включены 17 женщин с гиперплазией эндометрия без нарушений функции щитовидной железы. Во ІІ гр. были отнесены 33 женщины с гиперплазией эндометрия с нарушенной функцией щитовидной железы. Контроль- ную ІІІ гр. группу составили 12 здоровых женщин. Background. Among gynaecological pathology, from data of different authors, there are 17 to 59% of hyperplastic processes of endometrium. One from reasons of menstrual function disorders there is an Prolactinum increased level. From data of world literature, in 33% patients hyperprolactinemia develops on a background hypothyreoosis. Objective. There were observed 62 women in age from 18 to 55 years, delivered in two randomized groups. In I gr. 17 women were included with endometrial hyperplasia without disorders of thyroid gland function. In II gr. 33 women were taken with endometrial hyperplasia with disordered function of thyroid. Control group was made by 12 healthy women.
Influence of thyroid gland function of endometrium in women of reproductive age
Вплив функції щитовидної залози на гіперпластичні процеси ендометрію у жінок репродуктивного віку
Keywords: гиперплазия эндометрия; гипотиреоз; рецепторы; гормоны; hyperplasia of endometrium; hypothireosis; receptors; hormons